Translating and performing (in isiZulu) the poetry of psalm 134, using the literary-rhetorical approach - Dickie, June (Journal for Semitics, 2017)
The translation of poetry requires attention to the literary and rhetorical features of the source text. Moreover, all the functions achieved by the poetic devices in the source text must be fulfilled by similar or other poetic devices in the receptor language. In this empirical study, Psalm 134 is analysed for its literary and rhetorical features, following the steps delineated by Wendland (2004). Various experimental translations, composed by isiZulu mother-tongue speakers are then discussed, as well as the performances of these poems (as songs, rap, or spoken poetry). The translations are evaluated on the basis of functional translation, using the traditional criteria of accuracy, naturalness, and clarity, as well as the additional criteria of artistry, aurality, and acceptability.
free